THE CHILD’S RIGHT TO LIVE: NAVIGATING THE ETHICAL AND LEGAL CROSSROADS OF PARENTAL CONSENT AND MEDICAL NECESSITY IN NIGERIA - Victor, Aneke Chiagozie; Igwenyi, Benjamin; Udude, Kevin O. (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The doctrine of informed consent, a cornerstone of medical ethics, empowers competent individuals to steer their own healthcare journey. However, this principle faces a profound ethical crucible when applied to minors, whose autonomy is legally entrusted to parents or guardians. This delegation of authority becomes a matter of life and death when parental decisions, often rooted in sincere religious conviction, directly threaten a child’s survival. This paper argues that Nigerian jurisprudence has decisively established a hierarchy of rights where the preservation of a child’s life supersedes absolute parental autonomy. Through a comprehensive doctrinal analysis of statutory frameworks and pivotal case law, most notably the landmark Supreme Court decision in Esabunor & Anor. v. Dr. Tunde Faweya & Ors, this paper chronicles the legal evolution from parental absolutism to the state’s protective parens patriae role. It explores the delicate balance between the constitutional rights to religious freedom and the inviolable right to life, particularly for society’s most vulnerable. The paper concludes that the “best interests of the child” standard, with the right to life as its paramount component, must remain the unwavering compass guiding medical consent for minors in Nigeria. It recommends further legislative clarity and clinical guidelines to support healthcare providers navigating these agonizing dilemmas.